Impact of Flue Gas Species and Temperature on Mercury Oxidation - 陶叶 禚玉群 张亮 陈昌和 徐旭常 (Tsinghua science and technology, 2010)
Systematic experimental research has been conducted in a fixed-bed reactor system to determine the impact of coal-fired flue gas species and temperature on mercury oxidation. This work focuses on the temperatures range of 200℃ to 800℃ to demonstrate that temperature is a critical factor for the effect of the gas components on the mercury oxidation process. Among the investigated gases, hydrogen chloride is es- sential for oxidizing the elemental mercury. Nitrogen oxide was also found to have a positive correlation with the mercury oxidation when hydrogen chloride was present. Sulfur dioxide can either promote or inhibit the oxidation depending on the conditions; however, when nitrogen oxide is also present, sulfur dioxide has a negative impact. Ammonia exhibits an strong inhibitory effect. Several plausible mercury oxidation pathways are suggested in this paper.